The effects of cobalt elements addition on Ti2Ni phases, thermodynamics parameters, crystal structure and transformation temperature of NiTi shape memory alloys - Kok, Mediha; Zardawi, Hanaa Shahab Ahmed; Qader, Ibrahim Nazem; Kanca, M. Sait (Springer Heidelberg, 2019)
.By adding cobalt into NiTi-based shape memory alloy, the change of phase transformation, microstructure, and magnetic property of alloys has been investigated in austenite and martensite phases. NiTi and NiTiCo alloys with various rates of cobalt element, 2-6at.%, were prepared by arc-melting furnace, which had a high-vacuum level to avoid contamination, and then samples homogenized at 1323K for 24h. Subsequently, at room temperature each crystal structure, the microstructural phases, change in chemical composition ratio, and magnetization of the alloys, were investigated by using XRD, optical microscope, SEM-EDX, and PPMS equipment, respectively. The results of these measurements showed that, at room temperature, NiTiCo alloys with cobalt compositions of 0, 2, and 3 (at.%) exhibit the austenite phase, while the rest of the alloys show the martensite phase. Also, the enthalpy change for the first three alloys increased with increasing cobalt addition, however its value decreased suddenly for NiTiCo alloys with 4, 5, and 6 (at.%) cobalt doping.
Keywords: Mechanical-Properties; Corrosion Behavior; Microstructure; Cu; Ti